MENINGIOMAS IN DOGS: EPIDEMIOLOGY, ADVANCEMENTS IN DIAGNOSTIC IMAGING AND THERAPEUTIC OPTIONS - Sorin Marian Mârza; Radu Lăcătuș; Felix Daniel Lucaci; Robert Cristian Purdoiu (Agricultura)
The objective of this review was to synthesize existing research on canine meningiomas, focusing on their epidemiology, advancements in diagnostic imaging, and therapeutic options. We conducted a comprehensive literature search of databases including PubMed, Scopus, and Google Scholar, spanning publications from 2001 to 2021. The review specifically analyzed peer-reviewed studies that discussed new imaging techniques and treatment outcomes, including surgical resection and radiation therapy. Our findings indicate that canine meningiomas are most prevalent in older and larger breeds, with MRI emerging as a crucial tool for enhancing diagnostic accuracy. Surgical removal remains the primary treatment, achieving favorable outcomes. However, challenges persist in managing tumor recurrence and malignant forms, highlighting a need for further research into genetic markers and new therapeutic approaches. This review underscores the necessity for advanced diagnostic capabilities and tailored treatment strategies to improve prognosis and quality of life in affected dogs.